Structural-Geometric Functionalization of the Additively Manufactured Prototype of Biomimetic Multispiked Connecting Ti-Alloy Scaffold for Entirely Noncemented Resurfacing Arthroplasty Endoprostheses. (13th July 2017) - Uklejewski, Ryszard; Winiecki, Mariusz; Rogala, Piotr; Patalas, Adam
Abstract : The multispiked connecting scaffold (MSC-Scaffold) prototype, inspired by the biological system of anchorage of the articular cartilage in the periarticular trabecular bone by means of subchondral bone interdigitations, is the essential innovation in fixation of the bone in resurfacing arthroplasty (RA) endoprostheses. The biomimetic MSC‐Scaffold, due to its complex geometric structure, can be manufactured only using additive technology, for example, selective laser melting (SLM). The major purpose of this work is determination of constructional possibilities for the structural-geometric functionalization of SLM‐manufactured MSC‐Scaffold prototype, compensating the reduced ability—due to the SLM technological limitations—to accommodate the ingrowing bone filling the interspike space of the prototype, which is important for the prototype bioengineering design. Confocal microscopy scanning of components of the SLM‐manufactured prototype of total hip resurfacing arthroplasty (THRA) endoprosthesis with the MSC‐Scaffold was performed. It was followed by the geometric measurements of a variety of specimens designed as the fragments of the MSC-Scaffold of both THRA endoprosthesis components. The reduced ability to accommodate the ingrowing bone tissue in the SLM‐manufactured prototypes versus that in the corresponding CAD models has been quantitatively determined. Obtained results enabled to establish a way of compensatory structural‐geometric functionalization, allowing the MSC‐Scaffold adequate redesigning and manufacturing in additive SLM technology.